The archival turn: rereading the Guy Butler Collection in the National English Literary Museum - Wyrill, Beth (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2020)
This thesis takes as its theoretical springboard the 'archival turn' in South African historical studies, a moment that arguably reached its culmination in 2002 with the publication of Refiguring the Archive. The archival turn posits that, rather than using it as an unproblematic source of original material, scholars might begin to investigate the archive itself, including its processes of construction and organisation. This theoretical model also proposes that the archive might reflect the cultural beliefs and epistemologies common to the era in which it was set up. It seems that the time is ripe for a reconsideration of the insights gleaned from this academic moment in South Africa, given the recent contestation over the meanings of history and our cultural markers of heritage in the public domain, largely grouped under the term 'Fallism.' As such, a fresh look at South African museums, which in this country are often rooted in colonial practices of knowledge production, seems apt. This work uses the case of Guy Butler, founder of many South African English cultural institutes and arts bodies, as a conduit and lens for thinking through these problematics. One of Butler's institutional 'offspring,' born from his overarching work on behalf of the English cultural and literary cause in South Africa in the twentieth century, is the National English Literary Museum (NELM). Investigating the founding context and practices of NELM is a useful way of exploring the impact of Butler's life's work on literary heritage in South Africa. Issues such as the way in which NELM and Grahamstown continue to signify as loci of thought and practice in the contemporary South African literary landscape will be addressed. The study draws extensively on the Butler collection at NELM, and spends much time investigating Butler's positioning in a South African literary historical context in the twentieth century, to better understand the forces at work during the time of NELM's coming-into-being. Derrida's seminal work on the function of archives, in Archive Fever, is mined for a theoretical basis for the study, as is Deleuze and Guattari's thought on how bodies (taking the NELM institution here to represent a 'body') form, change, and interact, explicated in the work A Thousand Plateaus. The study offers some insights into how the NELM archive was formed, and which forces continue to shape its work in the South African spheres of English literature and heritage.
Keywords: National English Literary Museum (South Africa); Butler, Guy, 1918-2001; Archives -- South Africa; Archives -- Philosophy; Memory (Philosophy)